Effect of organic fertilizers combined with benzo (1,2,3) thiadiazole-7-carbothioic acid S-methyl ester (BTH) on the cucumber powdery mildew and the yield production - Bayoumi, Yousry A.; Hafez, Yasser M. (Acta Biologica Szegediensis, 2006)
Organic fertilizers such as compost, compost tea and seaweed extracts (Algean) combined with benzo (1,2,3) thiadiazole-7-carbothioic acid S-methyl ester (BTH)) showed significant effect on the powdery mildew-infected cucumber leaves with Sphaerotheca fuliginea. We have shown that spraying the infected cucumber leaves with the BTH (0.05 mM) combined with the organic fertilizers strongly decreased the disease severity of the cucumber powdery mildew fungus from 85.1% to 3.4% as compared to the control leaves which infected only with the pathogen. Furthermore, organic fertilizers combined with BTH increased significantly vegetative growth characters of cucumber (stem length, number of leaves /plant, leaf area /plant and chlorophyll content) especially at the earlier stage of growth as compared to the control plants (chemical fertilizer only). Also, most of the organic materials produced the highest cucumber early yield and fruit quality, but total yield was equal or less than the chemical fertilizers. Interestingly enough, that organic fertilizers combined with BTH elevated the ascorbic acid content (chemical quality of cucumber fruits) and decreased the nitrate content which very harmful as well as increased the fruit yields as compared to the control plants.